PROFESSORES DE ESCOLA PANTANEIRA - AQUIDAUANA - MS, BRASIL: NARRATIVAS DE MEMÓRIAS DO COTIDIANO - APARECIDA ALESSANDRA DE OLIVEIRA FARIA (2022)
ABSTRACT The present research refers to a study carried out with teachers of a Pantanal School in the city of Aquidauana, state of Mato Grosso do Sul, Brazil. It seeks to understand, through the narratives of these teachers' memories, the everyday scenes that permeate their life and work histories at school, in the Pantanal region of Aquidauana-MS-Brazil. The memories and narratives reported by the teachers were analyzed under the optics of cultural studies and describe the memories of the teachers of Escola Pantaneira as an approach factor of cultural growth, using the senses to know things, presenting the individual and collective needs before the process of ideological and epistemic construction, generating concrete relations through language when describing the trajectory as a subject that develops its alterity. It was possible to know the intrinsic possibilities of the subject being represented by the memory, which takes us to a world full of riches and wisdom, this process of knowledge interaction that people bring with themselves when in contact with the other, generating infinite ideas based on the concepts of culture providing new transformations and allowing us to get in touch with the reality of culture and teaching in the Pantanal region. Therefore, the narratives in the teaching work in face of their pedagogical practices serve as stimulating elements that induce teachers in general to reflect on their own profession. Thus, to analyze the narratives the researcher needs to be aware that the memory revealed by the subject will be selective presenting the facts, people, and situations that were relevant at the moment suggested. This is an exploratory-descriptive, cross-sectional study. The research data was collected in the second semester of the year 2021, with the participation of 6 elementary school teachers. The instrument used for data collection was a Socio-Demographic Occupational Questionnaire (QSDO) that was specially designed for this study, along with a semi-structured face-to-face interview. In view of this reality, concepts such as education in the field, teachers of pantanal school, narratives, memories, daily life, teaching work, Pantanal, pantanal culture under an analysis of the Cultural Studies theory are highlighted in this research. Keywords: Teachers, Pantanal School, Memories, Narratives, Cultural Studies.